Does the Expansion of Public Child Care Increase Birth Rates? Evidence from a Low-Fertility Country - Stefan Bauernschuster; Timo Hener; Helmut Rainer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Germany has the lowest birth rate among all OECD countries. To encourage fertility, the federal government has recently introduced a set of reforms that led to a substantial expansion of public child care for under three year old children. Using administrative county-level data, we exploit within-county variation in this expansion and find evidence that the provision of public child care causes an increase in birth rates. Extended empirical specifications suggest that our results are neither confounded by selective migration nor driven by tempo effects. Our analysis therefore provides some first evidence that low fertility may be reversed through changes in public policy that allow women to combine employment and motherhood.
Keywords: J13; D10; H31; 330